Prevalence and Risk Factors of Anxiety, Depression, and Sleep Problems Among Caregivers of People Living With Neurocognitive Disorders During the COVID-19 Pandemic - Li, Qiuxuan; Zhang, Haifeng; Zhang, Ming; Li, Tao; Ma, Wanxin; An, Cuixia; Chen, Yanmei; Liu, Sha; Kuang, Weihong; Yu, Xin; Wang, Huali (Frontiers in Psychiatry, 2021)
OBJECTIVE: To estimate the prevalence of mental health problems and associated factors among caregivers of neurocognitive disorders during the COVID-19 epidemic in China. METHODS: From March 1 to 31, 2020, 160 caregivers of older adults with dementia or mild cognitive impairment participated in an online cross-sectional survey on mental health problems, i.e., anxiety, depression, and sleep problems. The 7-item Generalized Anxiety Disorder Scale (GAD-7) was administered to measure anxiety levels, and the 2-item Patient Health Questionnaire (PHQ-2) was used to assess depressive symptoms. Six questions about COVID-19-related experiences were used to assess community-level infection contact and the level of exposure to media information. The prevalence rate of anxiety and depression was computed. Univariate and multivariate analyses were performed to investigate factors associated with single and multiple mental health problems. RESULTS: The prevalence rate of anxiety, depression, and sleep problems was 46.9%, 36.3%, and 9.4%. Approximately 55 participants (34.4%) presented with multiple mental health problems. Women had a higher risk of developing anxiety (OR, 5.284; 95% CI, 2.068-13.503; p=0.001). Having a mental disorder (OR, 5.104; 95% CI, 1.522-17.114; p=0.008) was associated with increased depression risk. Caregivers who preferred positive information (OR, 0.215; 95% CI, 0.058-0.793; p=0.021) was associated with decreased risk of sleep problem. CONCLUSION: Anxiety and depression were prevalent among caregivers of older adults with dementia or mild cognitive impairment during the COVID-19 epidemic. Being female was an independent risk factor for experiencing anxiety. Preexisting mental disorders increased the risk of depression among caregivers, while access to positive media information decreased sleep problems.